Internet Applications in Product Design and Manufacturing - Huang, George Q.; Mak, K. L. (Springer Berlin Heidelberg, 2003)
This book deals with Web applications in product design and manufacture, thus filling an information gap in digital manufacturing in the Internet era. It helps both developers and users to appreciate the potentials, as well as difficulties, in developing and adopting Web applications. The objective is to equip potential users and practitioners of Web applications with a better appreciation of the technology. In addition, Web application developers and new researchers in this field will gain a clearer understanding of the selection of system architecture and design, development and implementation techniques, and deployment strategies. The book is divided into two main parts. The first part gives an overview of Web and Internet and the second explains eight typical Web applications